Accumulated Testimony: Layering French Girls’ Diaries on the Algerian Exodus - Amy L Hubbell (Studies in 20th & 21st Century Literature, 2014)
In 1997, French-Algerian author Leïla Sebbar published an illustrated children’s book, J’étais enfant en Algérie, juin 1962 (‘I was a child in Algeria, June 1962’) in which she creates the fictional account of a young girl from the interior of Algeria leaving her home during the great exodus of the French just prior to Algerian independence. Using the genre of diary writing, Sebbar’s text reads as testimonial of fleeing their country for a homeland they do not know. Although this text is intimate, Sebbar relies on accumulated scraps of collective experience that, when joined to her own, fill in the absence of her homeland. In 2013, French artist Nicole Guiraud published her personal diaries kept before and during her exodus from Algeria from April to July 1962. Her raw representation of traumatic upheaval is couched in a rich paratext including artwork, photographs, and German translations, that simultaneously intensifies her account and distracts the reader from the extreme pain behind her words. In this article I demonstrate how fictional and real accounts published in very different historical contexts convey the exodus experienced by almost one million individuals and how each author deploys a layering technique to simultaneously draw in and distance the reader from extraordinarily painful personal experience.
Keywords: testimony; Algeria; Pieds-Noirs; exodus; Algerian War; trauma; Leïla Sebbar; Nicole Guiraud; collective memory